A convenient enantioselective decarboxylative aldol reaction to access chiral α-hydroxy esters using β-keto acids - Duan, Zhiqiang; Han, Jianlin; Qian, Ping; Zhang, Zirui; Wang, Yi; Pan, Yi (Beilstein Journal of Organic Chemistry, 2014)
We show a convenient decarboxylative aldol process using a scandium catalyst and a PYBOX ligand to generate a series of highly functionalized chiral α-hydroxy esters. The protocol tolerates a broad range of β-keto acids with inactivated aromatic and aliphatic α-keto esters. The possible mechanism is rationalized.
Keywords: enantioselective synthesis; hydroxy esters; scandium